Pemberdayaan Kelompok Tani Bangkit melalui Pembuatan Sabun Serai Wangi dan Label Kemasan Produk - Caroko, Novi; Surono, Untoro Budi; Zaki, Ahmad (Universitas Muhammadiyah Yogyakarta, 2025)
Essential oils are one of the vegetable oils that have many benefits. Kelompok Tani Bangkit is one of the Micro, Small, and Medium Enterprises (MSMEs) engaged in producing essential oils made from citronella plants. The production of derivative products in herbal bath soap offers a broader marketing opportunity than pure citronella oil. The purpose of this community service is to improve the understanding of the members of the Kelompok Tani Bangkit regarding the process of making herbal bath soap and product packaging labels. The implementation of this community service used the Participatory Rural Appraisal (PRA) method, which directly involved the community in every activity. The results of the community service showed that the knowledge of the members of the Kelompok Tani Bangkit regarding the making of herbal bath soap and product packaging labels increased by 73% and 72%, respectively